MANAJEMEN KESEHATAN MENTAL SANTRI MELALUI SISTEM KESADARAN DAN DUKUNGAN DI PESANTREN MODERN AT-TAUHID SUMBAWA - Sodikin, Satria; Marno; Mohammad Asrori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mental health plays a crucial role in the teaching and learning process, particularly in Islamic boarding schools (pesantren) that implement a 24 hour dormitory system. Therefore, maintaining students’ mental health is essential to ensure effective educational activities. Previous studies indicate that religiosity is closely related to mental health, and it is widely believed that pesantren can help adolescents develop stronger religiosity while providing awareness and support for mental well-being. Many parents enroll their children in pesantren with the expectation that they will grow into positive individuals in the future. This study aims to examine the mental health guidance system for students and to strengthen awareness and support regarding the importance of students’ mental health at the Modern Islamic Boarding School At-Tauhid Sumbawa. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation, which were then analyzed using qualitative descriptive methods. The findings reveal several forms of mental health awareness and support systems: (1) the input stage, including in-depth psychological interviews with prospective students and their parents or guardians and intensive training for new teachers; (2) the process stage, including counseling guidance provided by student caregivers and homeroom teachers as well as religious and extracurricular activities; (3) the output stage, which reflects the development of strong character and mental well-being, where students are sent to various pesantren with scholarships to continue their senior high school education on the island of Java and are able to compete successfully in both academic and non-academic activities; and (4) the evaluation stage, consisting of overall evaluations conducted by the pesantren leadership.